Molecular Feminisms: biology, becomings, and life in the lab - Roy, Deboleena (Seattle University of Washington Press, 2018)
(3z(BShould feminists clone?(3y z(BWhat do neurons think about?(3y z(BHow can we learn from bacterial writing?(3y (BThese and other provocative questions have long preoccupied neuroscientist, molecular biologist, and intrepid feminist theorist Deboleena Roy, who takes seriously the capabilities of lab (3z(Bobjects(3y$1 (Bbacteria and other human, nonhuman, organic, and inorganic actants$1 (Bin order to understand processes of becoming.s
Keywords: Women in science; Feminist theory; Feminism and science